STRATEGY FOR IMPROVING THE EFFECTIVENESS OF MANAGEMENT IN THE KARIMUNJAWA NATIONAL PARK CONSERVATION AREA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Karimunjawa National Park (TNKJ) is included in the national action plan for the management of conservation areas in 2018-2025. The objective of this research is to assess the effectiveness of the management of the TNKJ conservation area based on assessment guidelines in Indonesia, then the effective strategic recommendation is obtained for increasing the effectiveness of the management of the TNKJ conservation area. The study were conducted in August-December 2019. The assessment methods were used in this research are a score card for the Management Effectiveness Tracking Tool (METT) guideline, Management Effectiveness Evaluation guidelines for Marine Conservation Areas in Indonesia (COREMAP II - LIPI) and the building block assessment method for the Technical Effectiveness Evaluation guidelines Management of Marine, Coastal and Small Islands Conservation Areas (E-KKP3K). The results showed the assessment of the management of the TNKJ conservation area was considered as the most effective based on METT guidelines, COREMAP II - LIPI guidelines and the green status by E-KKP3K guidelines. The analysis is carried out by using the Analytic Network process (ANP) method. The implementation of the zoning system was been the main problem of the TNKJ management. Public and tourist awareness of the risk of waste and environmental damage were being the best solution for increasing the effectiveness of the management of the TNKJ.